Genotyping of Human Cytomegalo Virus Envelop Glycoprotein B in Iraqi Immunocopromised and immunosupresser Patients - Raghad Harbi Mahdi Al-Azzawi (Journal of Global Pharma Technology, 2016)
Envelope glycoprotein B is a surface protein of CMV which plays an important role in the pathogenesis of the virus, polymorphism in the gB gene may interfere with transmission of infection. This study was aimed to investigate the HCMV glycoprotein B genotypes in immunosupressed and immunocompromised Iraqi patients. A total of 362 Iraqi patients were collected from immunosupressed (pregnant women and infants) and immunocompromised (renal transplant and malignancies patients) that have been tested for the presence of acute infection of HCMV, during the period from November 2014 to February 2015. While another 20 individuals with negative serum IgM/IgG were included as negative control. The blood samples were positive for CMV-IgM and both IgM /IgG by ELISA and ELFA were found to be present in 85 (23.48 %) out of 362 blood samples. Five PCR confirmed isolates were chosen randomly for DNA sequences and similarity. Searches were carried out with the Basic Local Alignment Search Tool (BLAST) in National Center of Biotechnology Information (NCBI). The data showed that the glycoprotein B type 2 was the most common genotypes among the studied immunocoprimised and immunosupressed Iraqi patients. The nucleotide sequences of the glycoprotein B UL55 region from HCMV in this study have been deposited in the Gen Bank sequence database of HCMV under the following accession numbers: M17209.1, KP745721.1 and X17403.1.